2006
DOI: 10.1097/01.phm.0000202095.51037.a3
|View full text |Cite
|
Sign up to set email alerts
|

Burn Rehabilitation

Abstract: Esselman PC, Thombs BD, Magyar-Russell G, Fauerbach JA: Burn rehabilitation: State of the science. Am J Phys Med Rehabil 2006;85:383-413.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(43 citation statements)
references
References 308 publications
(325 reference statements)
0
42
0
1
Order By: Relevance
“…The knowledge that one will likely (repeatedly) be exposed to dangerous or threatening events will very likely have an effect on CSE and its associations with any experienced PTSD symptoms. It would also be interesting to see whether the same mechanisms are found in groups where lasting physical symptoms such as scars, chronic pain and functional impairment (Esselman et al, 2006;Summer et al, 2007) also play an important role, as for instance would be the case with burn victims. Additional research that investigates whether relationships between CSE and PTSD change when individuals are exposed to additional potentially traumatic events would also offer new insights into the ability of CSE to predict reactions to subsequent stressors.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…The knowledge that one will likely (repeatedly) be exposed to dangerous or threatening events will very likely have an effect on CSE and its associations with any experienced PTSD symptoms. It would also be interesting to see whether the same mechanisms are found in groups where lasting physical symptoms such as scars, chronic pain and functional impairment (Esselman et al, 2006;Summer et al, 2007) also play an important role, as for instance would be the case with burn victims. Additional research that investigates whether relationships between CSE and PTSD change when individuals are exposed to additional potentially traumatic events would also offer new insights into the ability of CSE to predict reactions to subsequent stressors.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…Currently, elastic compression using elastic garments is the predominant means of both prophylaxis and treatment for HTSs (63), despite controversial evidence-based data about their value in reducing the prevalence or magnitude of scarring (63). In fact, studies investigating pressure garments have found no significant difference between treatments involving the use of high-pressure garments, lower-pressure garments, or no pressure at all (64).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies investigating pressure garments have found no significant difference between treatments involving the use of high-pressure garments, lower-pressure garments, or no pressure at all (64). Others, however, claim that pressure therapy achieves HTS regression success rates of 60% to 85% (63), without any conclusive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Although existing data are scarce regarding emotional disturbance in fire survivors without physical injury, it is not uncommon for burn survivors to report psychological symptoms. Studies have demonstrated prevalence rates of 7–46% for depression and 9–45% for PTSD up to 1 year following burn injury (11, 48). In a retrospective study of 492 burn patients, symptom severity was significantly increased in those individuals who reported persistent pain up to 11 years after their injury.…”
Section: Discussionmentioning
confidence: 99%
“…Fire survivors are often subject to significant emotional trauma related to the event itself (10). It is estimated that 20–45% of burn survivors experience post-traumatic stress disorder (PTSD), associated with delusional memories, nightmares, and pain (11). Schneider et al demonstrated emotional trauma to be more significant than physical injury in predicting long-term impairments in quality of life for survivors of The Station nightclub fire (12).…”
Section: Introductionmentioning
confidence: 99%